Construction of high‐density genetic linkage map and mapping quantitative trait loci (QTL) for flowering time in autotetraploid alfalfa (Medicago sativa L.) using genotyping by sequencing. Issue 3 (26th September 2020) - Zhang, Fan; Kang, Junmei; Long, Ruicai; Yu, Long‐Xi; Sun, Yan; Wang, Zhen; Zhao, Zhongxiang; Zhang, Tiejun; Yang, Qingchuan
Abstract: Flowering time is an important agronomic trait of alfalfa ( Medicago sativa L.). Managing flowering time can produce economic benefits for farmers. To understand the genetic basis of this trait, quantitative trait loci (QTL) mapping was conducted in a full‐sib population that consisted of 392 individuals segregating based on flowering time. High density linkage maps were constructed using single nucleotide polymorphism (SNP) markers generated by genotyping‐by‐sequencing (GBS). The linkage maps contained 3, 818 SNP markers on 64 linkage groups in two parents. The average marker density was 4.33 cM for Parent 1 (P1) and 1.47 cM for Parent 2 (P2). Phenotypic data for flowering time was collected for three years at one location. Twenty‐eight QTLs were identified associated with flowering time. Eleven QTLs explained more than 10% of the phenotypic variation. Among them, five main effect QTLs located on linkage group (LG) 7D of P1 and five main effect QTLs located on LG 6D of P2 were identified. Three QTLs were co‐located with other QTLs. The identified linked markers to QTLs could be used for marker‐assisted selection in breeding programs to develop new alfalfa varieties to modulate flowering time.